Al-Shura - Al-Raysuni, Ahmad (International Institute of Islamic Thought, 2011)
Muslims remain largely unaware of the importance and value of the Qur’anic principle of alShura (mutual consultation) and the significant role it can play in the advancement and reform of Muslim society. In this work, the author attempts to introduce and examine key meanings and practices of alShura, trace its historical evolution, and explore ways in which the principle can be introduced, institutionalized and applied in Muslim societies. There is no doubt that alShura has been sidelined throughout the Muslim world and the reasons for this are both historically and politically complex. According to the author, although much has been written on the subject, in reality it has been at best ineffectively applied and at worst heedlessly ignored. Even today it is a hotly contested issue. As alShura is increasingly associated with democratic participation in a decisionmaking process, debate has ignited with critics challenging the notion of equating the principle with western notions of democracy, with others claiming that the principle allows for a meaning that breaks the grip of centralized power. These and other issues are investigated with careful scholarship. AlRaysuni concludes that alShura should be adopted as a way of life for all Muslims to protect their interests and as a vital tool for reconstruction and reform. In doing so he addresses the subject from some intriguing new angles, giving insight into areas hitherto little, if at all, examined.